Indexes of flow and cross-sectional area of the middle cerebral artery using doppler ultrasound during hypoxia and hypercapnia in humans. - Poulin, M; Robbins, P (1996)
BACKGROUND AND PURPOSE: This study examined changes in cross-sectional area of the middle cerebral artery as assessed by changes in Doppler signal power during hypoxia and hypercapnia. In addition, it examined the degree of consistency among three indexes of cerebral blood flow and velocity: the velocity spectral outline (VP), the intensity-weighted mean velocity (VIWM), and an index of middle cerebral artery flow (P. VIWM). P. VIWM was calculated as the product of VIWM multiplied by the total power signal. Power is proportional to cross-sectional area of the vessel; this calculation therefore allows for any changes in this variable. METHODS: Four protocols were used, each repeated six times for six healthy adults aged 20.8 +/- 1.7 years (mean +/- SD). The first was a control protocol (A) with end-tidal PO2 (ETPO2) maintained at 100 mm Hg and ETPCO2 at 1 to 2 mm Hg above eucapnia throughout. The second was a hypoxic step protocol (B) with ETPO2 lowered from control values to 50 mm Hg for 20 minutes. The third was a hypercapnic step protocol (C) with ETPCO2 elevated from control by 7.5 mm Hg for 20 minutes. The fourth was a combined hypoxic and hypercapnic step protocol (D) lasting 20 minutes. A dynamic end-tidal forcing system was used to control ETPCO2 and ETPO2. Doppler data were collected and stored every 10 milliseconds, and mean values were determined later on a beat-by-beat basis. VP, VIWM, power, and P.VIWM were expressed as a percentage of the average value over a 3-minute period before the step. RESULTS: In protocols A and B, there were no changes in power and there were no differences between VP, VIWM, and P.VIWM. In C, at the relief from hypercapnia, there was a transient nonsignificant increase in power and a transient nonsignificant decrease in both VP and VIWM compared with P.VIWM. In D, during the stimulus period, VP was significantly higher than VIWM (paired t test, P < .05), but both indexes were not different from P.VIWM. In the period that followed relief from hypoxia and hypercapnia, the Doppler power signal was significantly increased by 3.8%. During this period, VP and VIWM were significantly lower than P.VIWM. CONCLUSIONS: At the levels of either hypoxia or hypercapnia used in this study, there were no changes in cross-sectional area of the middle cerebral artery, and changes in both VP and VIWM accurately reflect changes in P.VIWM. With combined hypoxia and hypercapnia, however, at the relief from the stimuli when there is a very large and rapid decrease in P.VIWM, power is increased, suggesting an increase in the cross-sectional area. During this period, changes in VP and VIWM underestimate the changes in P.VIWM.